Contact-mediated quenching for RNA imaging in bacteria with a fluorophore-binding aptamer - Sünbül, Murat; Jäschke, Andres (Angewandte Chemie. International edition, 2013)
Bind and shine: Sulforhodamine B was converted into a very efficient fluorescence turn-on probe exclusively by contact quenching. The fluorescence of the probe increases more than 100-fold upon binding to a sulforhodamine-binding RNA aptamer (SRB-2). The probe and the SRB-2 aptamer were used to monitor transcriptions in real-time and to image RNA in live bacteria.